IMPROVING STUDENTS ABILITY TO WRITE NARRATIVE TEXT THROUGH PICTURE SERIES - Hanifatul Hidayah; Herni Sri Mulyati; Dasep Suprijadi (PROJECT (Professional Journal of English Education), 2019)
The aims of this research are to find out the class situation and to know the advancement of students’ ability in the application of teaching writing narrative text by means of picture series. In the classroom, students frequently gripe and say if the teacher grants them the task to write in English, they could not do it even when there have not begun yet. They do not have self-confident, feeling afraid of doing wrong, do not know what to scribe and way to get started. For those reasons the teacher conducted Classroom Action Research through picture series, such as Cinderella and The Three Little Pigs as a medium of teaching Narrative Text. In collecting data, researchers used interview and test. The test is done before the action (pre-test) or cycle I and after the action (post-test) or cycle II. The outcome of the study show that which exists positive improvement in students' writing skills and classroom situation during teaching and studying process. Test results increased, from the initial test (done before the action) to posttests (done after the action). That the average value of the test outcome is 74. The highest value acquisition of disciples in the early condition is 80, and the lowest worth is 70. While in cycle II (final condition) the average value of students increases to 90, after the teacher uses media images, the highest score of disciples in the final condition is 94, and the lowest score is 88.